Rang and Dale's pharmacology - 4 0 16; Rang, H. P.;Dale, M. Maureen; 5 (Edinburgh ;;New York : Elsevier/Churchill Livingstone, 2012)
This edition sets out a clear route through pharmacology for the reader, from a molecular understanding of receptors and drug actions to the clinical use of the most important groups of drugs. It contains everything students need to know about pharmacology in their early years.
Section 1: General principles 1. What is pharmacology? 2. How drugs act: general principles 3. How drugs act: molecular aspects 4. How drugs act: cellular aspects-excitation, contraction and secretion 5. Cell proliferation, apoptosis, repair and regeneration 6. Cellular mechanisms: host defence 7. Method and measurement in pharmacology 8. Drug absorption and distribution 9. Drug metabolism and elimination 10. Pharmacokinetics 11. Pharmacogenetics, pharmacogenomics and 'personalised medicine' Section 2: Chemical mediators 12. Chemical mediators and the autonomic nervous system 13. Cholinergic transmission 14. Noradrenergic transmission 15. 5-Hydroxytryptamine and the pharmacology of migraine 16. Purines 17. Local hormones: cytokines, biologically active lipids, amines and peptides 18. Cannabinoids 19. Peptides and proteins as mediators 20. Nitric oxide Section 3: Drugs affecting major organ systems 21. The heart 22. The vascular system 23. Atherosclerosis and lipoprotein metabolism 24. Haemostasis and thrombosis 25. Haemopoietic system and treatment of anaemia 26. Anti-inflammatory and immunosuppressant drugs 27. The respiratory system 28. The kidney 29. The gastrointestinal tract 30. The control of blood glucose and drug treatment of diabetes mellitus 31. Obesity 32. The pituitary and the adrenal cortex 33. The thyroid 34. The reproductive system 35. Bone metabolism Section 4: The nervous system 36. Chemical transmission and drug action in the central nervous system 37. Amino acid transmitters 38. Other transmitters and modulators 39. Neurodegenerative diseases 40. General anaesthetic agents 41. Analgesic drugs 42. Local anaesthetics and other drugs affecting sodium channels 43. Anxiolytic and hypnotic drugs 44. Antiepileptic drugs 45. Antipsychotic drugs 46. Antidepressant drugs 47. CNS stimulants and psychotomimetic drugs 48. Drug addiction, dependence and abuse Section 5: Drugs used for the treatment of infections, cancer and immunological disorders 49. Basic principles of antimicrobial chemotherapy 50. Antibacterial drugs 51. Antiviral drugs 52. Antifungal drugs 53. Antiprotozoal drugs 54. Anthelminthic drugs 55. Anticancer drugs Section 6: Special topics 56. Individual variation and drug interaction 57. Harmful effects of drugs 58. Lifestyle drugs and drugs in sport 59. Biopharmaceuticals and gene therapy 60. Drug discovery and development.
Includes Internet access.;Previous ed.: 2007.
Includes bibliographical references and index.
Keywords: 2 -- 0; 6; Pharmacology.;Drug Therapy.;Pharmacology. -- 20; 20; 2